2006
DOI: 10.1007/s10549-006-9184-1
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 expression is associated with a basal-like phenotype in sporadic and hereditary breast cancer

Abstract: The role of caveolin 1 (CAV1), a structural component of caveolae in breast cancer is controversial, although most studies suggest that it functions as a tumor-suppressor gene. In addition, some studies have identified CAV1 as a marker of myoepithelial cells. Since myoepithelial markers are frequently expressed in breast carcinomas with a basal-like phenotype, which are frequently occurring tumors in women with BRCA1 germline mutations, we evaluated whether CAV1 was associated with a basal-like phenotype in 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
98
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(117 citation statements)
references
References 38 publications
(49 reference statements)
16
98
1
1
Order By: Relevance
“…To this end, Joshi et al [60] have recently shown phosphorylated caveolin-1 to co-operate with Rho/ROCK and FAK-dependent signalling pathways promoting tumour cell invasion and metastasis in breast cancer. Such studies are consistent with clinical data showing a positive correlation between caveolin-1 expression (although distinction between phosphorylated and nonphosphorylated forms not addressed) and poor patient survival in highly aggressive invasive breast cancers [42][43][44]61]. The induction of caveolin-1 and the presence of a pool of phosphorylated caveolin-1 in gefitinib treated TAM-R cells may have profound implications for the overall function of caveolin-1 in these cells and for the clinical management of tamoxifen-resistant breast cancers involving the use of EGF-R inhibitors [62].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…To this end, Joshi et al [60] have recently shown phosphorylated caveolin-1 to co-operate with Rho/ROCK and FAK-dependent signalling pathways promoting tumour cell invasion and metastasis in breast cancer. Such studies are consistent with clinical data showing a positive correlation between caveolin-1 expression (although distinction between phosphorylated and nonphosphorylated forms not addressed) and poor patient survival in highly aggressive invasive breast cancers [42][43][44]61]. The induction of caveolin-1 and the presence of a pool of phosphorylated caveolin-1 in gefitinib treated TAM-R cells may have profound implications for the overall function of caveolin-1 in these cells and for the clinical management of tamoxifen-resistant breast cancers involving the use of EGF-R inhibitors [62].…”
Section: Discussionsupporting
confidence: 88%
“…These include amongst others the activation of the EGFR/RAS/ERK signalling pathway, increased cell proliferation and cell migration, initiation of mammary gland dysplasia, enhanced anchorage independent growth and metastatic potential. Conversely, several clinico-pathological studies correlate caveolin-1 over-expression with aggressive features of certain breast cancers, most notably the basal-like and inflammatory invasive subtypes [42][43][44]. However, none of these studies have explored the functional role of caveolin-1 in the development of hormone resistant breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…While other genes may be derived from the analysis of large microarray datasets, the biologic relevance of these genes makes them plausible predictive markers for defining a population of breast cancers that may respond to a src-targeted therapeutic like dasatinib. In addition, both moesin and caveolin-1 have been identified as markers for basal breast cancers [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…5 More recently, a subgroup of lobular carcinomas has been shown to express high-molecular-weight cytokeratins, 41 however it remains to be determined whether these cases truly show a basal-like transcriptome. The majority of basal-like breast cancers lack or show low levels of ER and PR, lack HER2 protein overexpression and HER2 gene amplification, whereas they express genes and proteins usually found in 'basal'/myoepithelial cells of the normal breast including high-molecular-weight cytokeratins (5/6, 14 and 17), 17,19,21,42 P-cadherin, 43 caveolins 1 and 2, 44,45 nestin, 46 aB crystallin, 47,48 CD109, 49,50 and EGFR 17 and, in a minority of cases, harbor EGFR gene amplification 51 or aneusomy. 52 p53 immunohistochemical expression or TP53 gene mutations is observed in up to 85% of cases, 53,54 and alterations of the pRB and p16 G1/S cell-cycle checkpoint are remarkably prevalent in these cancers.…”
Section: What Is a Basal-like Breast Cancer?mentioning
confidence: 99%